Is Migration A Good Substitute For Education Subsidies? - Docquier, Frédéric 2000- (The World Bank, 2008)
Assuming a given educational policy, the recent brain drain literature reveals that skilled migration can boost the average level of schooling in developing countries. This paper introduces educational subsidies determined by governments concerned by the number of skilled workers remaining in the country. The theoretical analysis shows that developing countries can benefit from skilled emigration when educational subsidies entail high .fiscal distortions. However when taxes are not too distortionary, it is desirable to impede emigration and subsidize education. The authors investigate the empirical relationship between educational subsidies and migration prospects, obtaining a negative relationship for 105 countries. Based on this result, the analysis revisits the country specific effects of skilled migration upon human capital. The findings show that the endogeneity of public subsidies reduces the number of winners and increases the magnitude of the losses